The Spread of Helicoverpa armigera (Lepidoptera: Noctuidae) and Coexistence with Helicoverpa zea in Southeastern Brazil - Fábio A. Pinto; Marcos V. V. Mattos; Farley W. S. Silva; Silma L. Rocha; Simon L. Elliot (Insects, 2017)
Helicoverpa armigera, one of the world’s most destructive crop pests, was first documented in Brazil in 2013. Within a few months, this polyphagous insect had spread over the Northeast and Central-West of Brazil, causing great agricultural losses. With several reports of populations resistant to pesticides and Bt crops around the world, there is great concern about the spread of this pest in Brazil. There is confusion about the actual distribution of this species due to the high morphological similarity with the native corn earworm Helicoverpa zea, which may also coexist with H. armigera in the field. Our aims here were (i) to confirm its presence in the State of Minas Gerais, one of the most important agricultural regions in the country; and (ii) to assess the co-occurrence of this pest with the congeneric corn earworm H. zea. Using molecular screening, we confirmed the presence of H. armigera in Bt-crops of soybean and cotton, and non-Bt-crops of soybean, cotton and maize. Mixed infestations of H. armigera with H. zea were found in non-Bt maize (Viçosa, Southeastern Minas Gerais). These results highlight the need for adequate control strategies for H. armigera in Brazil, to deal with its polyphagous feeding habits, high dispersal capacity and possible risks of hybridization with congeneric species.